Methanol Extract of Rue Leaves on Body Fat Composition, Insulin Resistance, and Leptin Gene Expression - Florensia Syntesa Haryta; Shanti Listyawati; Dono Indarto (Jurnal Kesehatan Masyarakat, 2026)
Obesity is a multifactorial and complex disorder characterized by excessive accumulation of adipose tissue, with negative health outcomes. Rue leaves (Ruta graveolens) contain active compounds that have activity as anti-obesity, such as rutacridone. Therefore, this study aims to determine the effect of Rue Leaves Methanol Extract (MER) on Obesity Index (OI), Body Fat Content (BFC), Wet Fat Weight (WFW), Insulin level (IL), Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), Homeostatic Model Assessment for β-cell Function (HOMA-β) and Leptin Gene Expression (LGE) in obesity model rats (OR). This study was an experimental animal study with a pretest-posttest control group design using 24 male Sprague-Dawley rats, which were randomly divided into six groups. The normal group (N) was male rats + standard rat feed (BR-2). The negative and positive groups (NC and PC) were OR + BR-2 + 1 mL 0.9% NaCl or 0.6 mg/kgBW pure rutacridone, respectively. Treatment groups (T1-T3) were OR + BR-2 + 80, 100, or 200 mg/kg BW MERL for 30 days. Our results demonstrated that MER administration significantly reduced OI, BFC, IL and HOMA-IR also significantly increased HOMA-β level with p ˂ 0.05, compared to the NC group in a dose-dependent manner. Our data also showed low expression of leptin gene and WFW in all treatment groups. In conclusion, MER administration reduces OI, BFC, WFW, IL, HOMA-IR and LGE while increasing HOMA-β in male obese rats.